Adaptive Watermarking Scheme Using Biased Shift of Quantization Index - Young-Ho Seo; Hyun-Jun Choi; Ji-Sang Yoo; Dong-Wook Kim (Journal of Electrical and Computer Engineering)
We propose a watermark embedding and extracting method for blind watermarking. It uses the characteristics of a scalar quantizer to comply with the recommendation in JPEG, MPEG series, or JPEG2000. Our method performs embedding of a watermark bit by shifting the corresponding frequency transform coefficient (the watermark position) to a quantization index according to the value of the watermark bit, which prevents from losing the watermark information during the data compression process. The watermark can be embedded simultaneously to the quantization process without an additional process for watermarking, which means it can be performed at the same speed to the compression process. In the embedding process, a Linear Feedback Shift Register (LFSR) is used to hide the watermark informations and the watermark positions. The experimental results showed that the proposed method satisfies enough robustness and imperceptibility that are the major requirements for watermarking.